Problems of monopoly and economic warfare - Zeuthen, F. (Frederick), 1888-1959. (London : Routledge and K. Paul, 1930)
Includes index
First published 1930 by George Routledge & Sons Ltd.
Keywords: Competition; Monopolies; Economics